Global research trends in penile cancer: Bibliometric and visualized analysis - Deng, Sheng; Xuan, Zhihua; Feng, Junlong; Li, Haisong; Wang, Bin; Yang, Zhen; Xuan, Lihua; Meng, Fanchao; Wang, Lu; Xiao, Yangchun; Wang, Jisheng (Frontiers in Oncology, 2023)
Background: Penile cancer is a malignant tumor of the genitourinary system that mostly occurs in middle-aged and elderly men aged 50–70 years, which can seriously affect physical, psychological, and sexual health. Hundreds of original articles and reviews on penile cancer are published each year. However, a bibliometric analysis of these publications has not been performed. Objective: This study aimed to systematically analyze and visualize penile cancer-related publications through bibliometrics and reveal identified topics, hotspots, and knowledge gaps in related fields. Methods: Based on the Web of Science core collection database, we first analyzed the quantity and quality of publications in the field of penile cancer. Second, we profiled the publishing groups in terms of country, institution, author’s publication, and cooperation network. Then, we systematized and summarized the hot topics of research. Results: This bibliometric analysis was conducted from 2001 to 2022. The analysis identified 1,687 articles and reviews, which were published in 432 journals. The number of publications and citations on penile cancer-related research has steadily increased over the last two decades. Furthermore, academic institutions in Europe and the United States play a leading role in penile cancer research. The country, institution, journal, and author with the most publications were the United States (507), H Lee Moffitt Cancer Research Center (96), Journal of Urology (83), and Spiess P (87), respectively. The most frequently used keywords were penile cancer (743), squamous-cell carcinoma (717), cancer (380), carcinoma (232), lymphadenectomy (229). 16 keyword clustering information was obtained, including #0 male circumcision, #1 lichen sclerosus, #2 chemotherapy, #3 penile neoplasms, #4 targeted therapy, #5 resection margin, #6 cervical cancer, #7 lymph node dissection, #8 prognostic factor, #9 prostate cancer, #10 inguinal lymph node dissection, #11 human papillomavirus DNA, #12 gene, #13 penile intraepithelial neoplasia, #14 male sexual function, and #15 penile cancer. Conclusion: More and more scholars are devoted to the research on penile cancer. This bibliometric analysis revealed that the main research topics and hotspots in penile cancer included risk factors and surgical treatment plans.